IN VITRO ENTRAPMENT AND RELEASE STUDIES OF LEVOFLOXACIN USING EPICHLOROHYDRIN-CROSSLINKED HYDROGEL - RESCOBER, ANGELI ANN S. (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to optimize and evaluate the controlled release rate, ocular irritancy, and in vitro antimicrobial properties of levofloxacin entrapped in the epichlorohydrin-crosslinked hydrogel of sodium carboxymethyl cellulose (NaCMC) and gelatin. Materials and Methods: Various parameters such as polymer ratio, amount of crosslinker, temperature, reaction time, swelling capacity, and percent drug loading were considered in Optimized levofloxacin hydrogel. Hydrogel preparations with higher amount of drug loaded were further analyzed to determine its in vitro drug release rate, ocular irritancy on New Zealand rabbits, and antimicrobial activities against Pseudomonas aeruginosa and Staphylococcus aureus. Optimized levofloxacin hydrogel (OLH) was then subjected to 3-month stability testing at 40 ± 2°C and 75 ± 5% relative humidity in which samples were withdrawn at the end of each month for analysis. Results: Polymer groups with higher concentrations of NaCMC have higher swelling and drug loading capacities than those with higher gelatin concentrations. Meanwhile, qualitative analysis using differential scanning calorimetry, Fourier-transform infrared spectroscopy, and scanning electron microscopy verified the presence of levofloxacin in the epichlorohydrin-cross-linked hydrogel. Among the four polymer ratio, F3 was the optimized hydrogel with drug-loaded concentration of 99.50%, which was within the acceptable assay limit of 0.5% levofloxacin solution based on United States Pharmacopeia monograph. It followed the Higuchi kinetic model with a drug release mechanism of super case 2 transport indicating hydrogel swelling as a key factor for its controlled drug release. In vitro, antibacterial test against P. aeruginosa and S. aureus was sensitive to optimized levofloxacin hydrogel (OLH) with inhibitory diameter zones of 31.68 and 37.05 mm, respectively. Ocular irritancy test also showed that the OLH is non-irritating on installation in the cul-de-sac of New Zealand rabbits. Conclusion: Optimized levofloxacin hydrogel was effective, non-irritating, and stable, which can be used as an alternative to conventional 0.5% levofloxacin ophthalmic solution.